Pedagogical Explications of Cultural Studies of Jerome Bruner - Sizov, Vitalii; Slavska, Yanina; Alforov, Oleksandr (Journal of History Culture and Art Research, 2024)
The article provides an overview of the pedagogical ideas of Jerome Bruner set out in the work “Culture of Education”. J. Bruner, being a representative of cognitive psychology, considers pedagogical processes from the standpoint of the cultural-historical theory of L. Vygotsky. The pedagogy of J. Bruner is based on the culture of that society in which a child’s thinking is formed. The article highlights three explicative characteristics of J. Bruner's pedagogy. The primary explication is the transition of Bruner’s cognitive psychology into the field of practical pedagogy. The second manifestation of Bruner’s theory explication is the culture concept in pedagogy, forms and methods of practical implementation of this concept. The third manifestation of J. Bruner’s pedagogical explication is the emphases in analysis of the theme of culture and education from the perspective of the relationship between positions of the collective and individual in the system of teaching and upbringing, and mainly the specificity of these relationships according to J. Bruner. In the review, all three manifestations of the pedagogical explication of J. Bruner are concretized in two main elements of J. Bruner’s scientific theory, the first one is the role of culture in the education system in general and in pedagogy in particular. And the second element is the practical reflection of the theme of culture in pedagogical forms and methods, as it is seen by J. Bruner. The article highlights the main idea of ​​J. Bruner that education is ensuring reproduction of the culture on the basis of which it arose. Moreover, not just to reproduce, but to be a conductor of economic, political and cultural goals inherent in a given society. This thesis constitutes the main meaning and spirit of the pedagogical explication of cultural studies of J. Bruner.